Konstruksi Plasmid Rekombinan untuk Inisiasi Translasi Enhance Green Fluorescent Protein oleh Internal Ribosomal Entry Site HIV-1 - Cintera Rahmagiarti; Silvia Tri Widyaningtyas; Budiman Bela (Media Penelitian dan Pengembangan Kesehatan, 2018)
Human immunodeficiency virus (HIV) is a virus that causes acquired immunodeficiency virus syndrome (AIDS). The HIV genome has a cap structure at 5’ and polyadenylation at 3’ on mRNA resulting in a translation initiation through scanning at 5'untranslated region (UTR). The Vpr protein produced during viral replication causes the 5'cap scanning to be inhibited so HIV-1 can directly recruit the ribosome at the start codon via internal ribosomal entry site (IRES). IRES activity is high at G2/M phase and highest expression in monocyte cell line (THP-1) and lymphocyte (HPB-ALL). The role of HIV IRES however, is not yet known in infection of nondividing cells by HIV-1. HIV-1 IRES and egfp from pcDNA5FRT/TO were amplified with PCR. The insert DNA (HIV-1 IRES_egfp) and pcDNA3.1(+) were digested with EcoRI and ApaI and then ligated. The verification was performed with PCR colonies, restriction verification, and sequencing. The size of insert DNA is 1067 bp while the vector is 5379 bp. E. coli transformed with DNA ligation produces 70 colonies, control of ligation produces 5 colonies, and negative control didn’t grow. 19 colonies contain recombinant DNA, restriction verification was of the appropriate size, and the sequence verification didn’t find any mutation. Therefore, the subcloning process pcDNA3.1_IRES HIV-1_egfp was successfully performed. Abstrak Human immunodeficiency virus (HIV) merupakan virus penyebab acquired immunodeficiency virus syndrome (AIDS). Genom HIV memiliki struktur cap di 5’ dan poliadenilasi di 3’ mRNA sehingga proses inisiasi translasi melalui pemindaian 5’cap pada struktur untranslated region (UTR) di 5’ mRNA HIV. Protein Vpr yang dihasilkan selama replikasi virus menyebabkan pemindaian melalui 5’cap terhambat sehingga HIV-1 dapat langsung merekrut ribosom pada kodon awal translasi melalui struktur internal ribosomal entry site (IRES). Aktivitas IRES tinggi pada fase G2/M dan ekspresi gen tinggi pada sel line monosit (THP-1) dan limfosit (HPB-ALL). Namun, peran IRES HIV-1 belum diketahui pada sel tidak membelah yang merupakan sel target pada infeksi HIV-1. DNA sekuen IRES HIV-1 dan egfp dari pcDNA5FRT/TO diamplifikasi dengan PCR. DNA sisipan (IRES HIV-1_egfp) dan pcDNA3.1(+) dipotong dengan EcoRI dan ApaI lalu DNA sisipan diligasi dengan pcDNA3.1(+). Verifikasi hasil klona dilakukan dengan PCR koloni, verifikasi restriksi, dan sekuensing. Restriksi DNA sisipan menghasilkan pita berukuran 1067 pb. Restriksi vektor plasmid menghasilkan pita berukuran 5379 pb. E.coli yang ditransformasi DNA ligasi menghasilkan 70 koloni, kontrol ligasi 5 koloni, dan kontrol negatif tidak tumbuh. 19 koloni terverifikasi mengandung DNA rekombinan, verifikasi restriksi memiliki ukuran sesuai, dan verifikasi sekuensing tidak terdapat perubahan basa. Oleh karena itu, proses subkloning pcDNA3.1_IRES HIV-1_egfp berhasil dilakukan.